Tithe : a modern faerie tale - Black, Holly (London : Simon & Schuster, 2008)
Sixteen-year-old Kaye, who has been visited by faeries since childhood, discovers that she herself is a magical faerie creature with a special destiny.
Young Adult.
Young Adult
Keywords: Fairies -- Fiction; Fantasy; Magic -- Fiction; Fairies -- Fiction; Magic -- Fiction; Fantastic fiction